2020
DOI: 10.1093/cid/ciaa1648
|View full text |Cite
|
Sign up to set email alerts
|

Flying Fox Hemolytic Fever, Description of a New Zoonosis Caused by Candidatus Mycoplasma haemohominis

Abstract: Background Hemotropic mycoplasmas, previously classified in the genus Eperythrozoon, have been reported as causing human infections in Brazil, China, Japan and Spain. Methods In 2017, we detected DNA from “Candidatus Mycoplasma haemohominis” in the blood of a Melanesian patient from New Caledonia presenting with febrile splenomegaly,weight loss, life-threatening autoimmune haemolytic anemia and hemophagocytosis. The full geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Fourteen of the 15 positive cases exhibited febrile autoimmune hemolytic anemia and hemophagocytosis. Comparative genome sequencing revealed that the average nucleotide identity (ANI) value between genomes of CMhh strain SWG34-3 reported by Hattori et al (2020) from a Japanese patient and CMhh strain Neocaledonica described by Descloux et al (2020) is ~98%, which is above the threshold for bacterial species delineation of ≥95% (Goris et al, 2007;Richter and Rosselló-Móra, 2009;Yoon et al, 2017), and therefore, demonstrates these two strains likely belong to the same species. Interestingly, most of the positive patients reported hunting and eating flying foxes, and closely related (up to 100%) 16s rRNA and dnaK genes sequences were detected in the flying foxes analyzed.…”
Section: Accepted Articlementioning
confidence: 95%
See 3 more Smart Citations
“…Fourteen of the 15 positive cases exhibited febrile autoimmune hemolytic anemia and hemophagocytosis. Comparative genome sequencing revealed that the average nucleotide identity (ANI) value between genomes of CMhh strain SWG34-3 reported by Hattori et al (2020) from a Japanese patient and CMhh strain Neocaledonica described by Descloux et al (2020) is ~98%, which is above the threshold for bacterial species delineation of ≥95% (Goris et al, 2007;Richter and Rosselló-Móra, 2009;Yoon et al, 2017), and therefore, demonstrates these two strains likely belong to the same species. Interestingly, most of the positive patients reported hunting and eating flying foxes, and closely related (up to 100%) 16s rRNA and dnaK genes sequences were detected in the flying foxes analyzed.…”
Section: Accepted Articlementioning
confidence: 95%
“…All rights reserved Eidolon fruit bats from Nigeria (Di Cataldo et al, 2020b) and Myotis chiloensis from Chile (Millán et al, 2019a). Recently, sequences with up to 100% identity to CMhh were identified in three Pteropus species in New Caledonia (Descloux et al 2020). However, many other sequences represent novel genotypes with variable similarity to previously identified hemotropic Mycoplasma species in other bats, ticks, rodents, primates, and carnivores (Becker et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in cooperation with the veterinary services of New Caledonia, the bacterial “Candidatus Mycoplasma haemohominis” species was recently detected in fruit bats of the Pteropus genus. This bacterium is responsible for haemolytic fever in humans, an emerging zoonosis [ 28 ].…”
Section: Investigations Conducted On Wild Animalsmentioning
confidence: 99%